Impelementasi Metode Simpleks Untuk Optimasi Penjualan Produk UKM Pada Masa Pandemi - Rumetna, Matheus Supriyanto; Lina, Tirsa Ninia; Salawe, Diosphyros; Irianti, Rezky; Buku, Gabriel Valentino; Lokollo, Sonia; Walalayo, Titalae; Sauyai, Yetti; Wayega, Ferdinandus; Karepouwan, Vincent (PETIR, 2022)
Small and Medium Enterprises (SMEs) are one of the businesses that have an important role in developing the economy in Indonesia. However, when the Covid-19 pandemic hit many SME players who had difficulty optimizing business activities. The Covid-19 pandemic is a major threat in all fields. Mrs. Martina’s SME is one of the SMEs that experienced a decline in profits during the Covid-19 pandemic. Some of the obstacles faced by Mrs. Martina are costs, transportation and distance. For the development of Mrs. Martina’s business, it is necessary to take steps to increase the profit from the sale. These steps must use a technique or method so that they have a more accurate estimate in the calculation. One of the methods that can be used is the Simplex method which is part of the Linear Program. This research has the main objective of helping SMEs, especially those owned by Mrs. Martina, in terms of optimizing sales results in order to increase profits. This research also utilizes information technology, namely POM-QM software, to make it easier to determine and calculate the maximum profit obtained from each production carried out by Mrs. Martina’s SME within one week quickly and accurately. The results obtained are used as reference material or benchmarks for SMEs in terms of making decisions for business development.